The Development of Electronics Book Combined with the QR Code Technology Titled in “Social Media Literacy” - Thamwipat, Kuntida; PRINCHANKOL, PORNPAPATSORN; Meekong, Jirapoom; Sriha, Siriyakorn (Siam Communication Review, 2021)
This research aimed to develop and find quality, assessment of perception and satisfaction of the sample group toward Electronics book combined with the QR code technology titled in “Social Media literacy ”, the research tools were as follows: 1) content evaluation form 2) media evaluation form for electronics book combined with the QR code technology 3) evaluation form of the sample's perception on electronics book combined with the QR code technology 4) evaluation form measuring subject group satisfaction to electronics book combined with the QR code technology. The sample group used for this evaluation consists of 30 people from 2nd year of undergraduate level from the department of Educational Communications and Technology who registered for the course of ETM 202 Advertising and Public Relations during the first semester of the academic year 2020 selected by purposive sampling method from the students who learned by the developed electronics book and pleased to response the questionnaires. The expert evaluation results showed that the content quality assessment was at a very good level. ( =4.70, S.D. = 0.40). The media quality evaluation result was at a very good level. ( =4.64, S.D. = 0.46) The evaluation of the perception of the sample was in at the highest level ( =4.54, S.D. = 0.59). And the satisfaction evaluation result of the sample group was at the highest level ( =4.57, S.D. = 0.56). Therefore, the developed electronics book were in a high quality and could be used practically